Tightly centromere-linked gene (SPO15) essential for meiosis in the yeast Saccharomyces cerevisiae. - Yeh, E (1986)
We used DNA fragments from the centromere regions of yeast (Saccharomyces cerevisiae) chromosomes III and XI to examine the transcriptional activity within this chromosomal domain. DNA transcripts were found 200 to 300 base pairs from the 250-base-pair centromere core and lie within an ordered chromatin array. No transcripts were detected from the functional centromere region. We examined the cellular function of one of these tightly centromere-linked transcripts. (CEN11)L, by disrupting the coding sequences in vivo and analyzing the phenotype of the mutant yeast cell. Diploids heterozygous for the (CEN11)L disruption sporulated at wild-type levels, and the absence of the (CEN11)L gene product had no effect on the viability or mitotic growth of haploid cells. Diploids homozygous for the (CEN11)L disruption were unable to sporulate when induced by the appropriate nutritional cues. The mutant cells were competent for intragenic recombination and appeared to be blocked at the mononucleate stage. The temporal ordering of (CEN11)L function with respect to the sporulation mutant spo13 suggests that the (CEN11)L gene product may be required at both the first and second meiotic cell divisions. This new sporulation gene has been termed SPO15.